Molecular Mechanisms of cGAS-STING Axis and Mitochondrial Dysfunction-Related Diseases in Humans: A Comprehensive Review - Shen, Xingtong; Chen, Hantao; Zheng, Jishan; Ma, Yunyan; Tang, Zhengzhen; Sun, Hongqin; Zhang, Qian; Zhang, Jidong; Song, Tao (Current Neuropharmacology, 2025)
Mitochondria play a critical role in immune cell differentiation, activation, and the regulation of innate immune responses. The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway is a key mediator of cytosolic DNA sensing and contributes to a broad spectrum of pathological processes, including infectious diseases, sterile inflammation, cancer, and autoimmune disorders. STING is activated in response to cytosolic DNA during infection and can restrict translation in RNA virus-infected cells as part of the innate immune response. Studies have shown that mitochondrial dysfunction, particularly the release of mitochondrial DNA (mtDNA), can act as a potent trigger of cGAS-STING signaling, linking mitochondrial damage to immune activation. Additionally, this pathway intersects with autophagy, metabolic regulation, and cell death mechanisms. This comprehensive review summarizes current advances in understanding the cGAS-STING axis and mtDNA release in the context of mitochondrial dysfunction, with a focus on their roles in disease pathogenesis and potential as therapeutic targets. We highlight recent progress in the development of targeted interventions and emphasize the importance of elucidating the regulatory mechanisms underlying STING activation in various pathological conditions, including neuroinflammation, cancer, ischemia/reperfusion injury, and autoimmune diseases.
Keywords: immune responses